2010
DOI: 10.1002/mop.25425
|View full text |Cite
|
Sign up to set email alerts
|

Temperature‐independent fiber bragg grating tilt sensor

Abstract: A novel fiber Bragg grating (FBG) tilt sensor is proposed to detect the magnitude and the direction of a two‐dimensional inclination by using four FBGs. High angle sensitivity and measurement resolution have been achieved, and the temperature effect has been eliminated completely without additional temperature compensation schemes. Experimental results verified the feasibility of the proposed idea. © 2010 Wiley Periodicals, Inc. Microwave Opt Technol Lett 52:2250–2252, 2010; Published online in Wiley InterScie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…Most conventional tilt sensors are of an electronic type, transforming the inclination into electronic signals through a magnetic effect [1][2][3][4] or a capacitive effect [5]. Comparing with those tilt sensors above, optical fiber tilt sensors [6][7][8][9][10][11][12][13] have important advantages of electrically passive operation and immunity to electromagnetic interference, and most of the sensors are based on fiber Bragg gratings (FBGs). The principle of these sensors is that the FBGs' reflective wavelength will shift with applied strains through transitive installations when working.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most conventional tilt sensors are of an electronic type, transforming the inclination into electronic signals through a magnetic effect [1][2][3][4] or a capacitive effect [5]. Comparing with those tilt sensors above, optical fiber tilt sensors [6][7][8][9][10][11][12][13] have important advantages of electrically passive operation and immunity to electromagnetic interference, and most of the sensors are based on fiber Bragg gratings (FBGs). The principle of these sensors is that the FBGs' reflective wavelength will shift with applied strains through transitive installations when working.…”
Section: Introductionmentioning
confidence: 99%
“…The principle of these sensors is that the FBGs' reflective wavelength will shift with applied strains through transitive installations when working. In the great majority of the tilt sensors based on the FBGs, the top ends of the FBGs are fixed on a frame while the bottom ends need to be bonded with a heavy mass [5][6][7][8][9][10]. These require the configuration of FBG-based tilt sensors to be more complex and delicate.…”
Section: Introductionmentioning
confidence: 99%
“…However, such methodologies are impractical for real-field applications, owing to their bulk/ complicated and expensive configurations. Recently, a few FBG based attempts have been made for inclination/tilt measurement [8][9][10][11][12][13][14]. Though a very high resolution was achieved [8], the performance in these studies was limited by the design constraints such as a cantilever based pendulum suspension mechanism resulting in friction and corresponding instabilities in [8,9,11] and predeflections of steel flakes with a complicated pendulum suspension mechanism in [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, retrieval of the tilt was based on a very intricate mathematical analysis. Ni et al [13] reported another tilt sensor based on four FBGs in series on a single fiber making an inverted pyramidal structure with four fiber arms and a mass (bob) suspended from the vertex. Nevertheless, stability of the sensor and the cross-sensitivity to unwanted perturbations in both the designs are important issues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation